[2 + 1] Cycloaddition reactions of fullerene C60 based on diazo compounds - Biglova, Yuliya N. (Beilstein Journal of Organic Chemistry, 2021)
The most common variant of fullerene core functionalization is the [2 + 1] cycloaddition process. Of these, reactions leading to methanofullerenes are the most promising. They are synthesized in two main reactions: nucleophilic cyclopropanation according to the Bingel method and thermal addition of diazo compounds. This present review summarizes the material on the synthesis of monofunctionalized methanofullerenes – analogues of [60]PCBM – based on various diazo compounds. The main cyclopropanating agents for the synthesis of monosubstituted methanofullerenes, the optimal conditions and the mechanism of the [2 + 1] cycloaddition, as well as the practical application of the target products are analyzed.
Keywords: [2 + 1]-cycloaddition processes; analogues of [60]PCBM; diazo compounds; mechanisms and optimal conditions of cyclopropanation; methanofullerenes C60